Neural hyperactivity in the amygdala induced by chronic treatment of rats with analgesics may elucidate the mechanisms underlying psychiatric comorbidities associated with medication-overuse headache - Wanasuntronwong, Aree; Jansri, Ukkrit; Srikiatkhachorn, Anan (My University, 2017)
Background: Patients with medication-overuse headache suffer not only from chronic headache, but often from psychiatric comorbidities, such as anxiety and depression. The mechanisms underlying these comorbidities are unclear, but the amygdala is likely to be involved in their pathogenesis. To investigate the mechanisms underlying the comorbidities we used elevated plus maze and open field tests to assess anxiety-like behavior in rats chronically treated with analgesics. We measured the electrical properties of neurons in the amygdala, and examined the cortical spreading depression (CSD)-evoked expression of Fos in the trigeminal nucleus caudalis (TNC) and amygdala of rats chronically treated with analgesics. CSD, an analog of aura, evokes Fos expression in the TNC of rodents suggesting trigeminal nociception, considered to be a model of migraine. Results: Increased anxiety-like behavior was seen both in elevated plus maze and open field tests in a model of medication overuse produced in male rats by chronic treatment with aspirin or acetaminophen. The time spent in the open arms of the maze by aspirin- or acetaminophen-treated rats (53 ± 36.1 and 37 ± 29.5 s, respectively) was significantly shorter than that spent by saline-treated vehicle control rats (138 ± 22.6 s, P < 0.001). Chronic treatment with the analgesics increased the excitability of neurons in the central nucleus of the amygdala as indicated by their more negative threshold for action potential generation (-54.6 ± 5.01 mV for aspirin-treated, -55.2 ± 0.97 mV for acetaminophen-treated, and -31.50 ± 5.34 mV for saline-treated rats, P < 0.001). Chronic treatment with analgesics increased the CSD-evoked expression of Fos in the TNC and amygdala [18 ± 10.2 Fos-immunoreactive (IR) neurons per slide in the amygdala of rats treated with aspirin, 11 ± 5.4 IR neurons per slide in rats treated with acetaminophen, and 4 ± 3.7 IR neurons per slide in saline-treated control rats, P < 0.001]. Conclusions: Chronic treatment with analgesics can increase the excitability of neurons in the amygdala, which could underlie the anxiety seen in patients with medication-overuse headache.
Keywords: Acetaminophen; Amygdala; Anxiety; Aspirin; Medication-overuse headache; Migraine